Proteomic and Ionomic Study for Identification of Biomarkers in Biological Fluid Samples of Patients with Psychiatric Disorders and Healthy Individuals - de Jesus, Jemmyson Romário; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book presents an exploratory analysis based on proteomic and ionomics studies comparing the blood serum of patients with bipolar disorder (BD), healthy controls, patients with schizophrenia (SCZ), and patients with other disorders (OD) in order to identify biomarkers of BD. Bipolar disorder is a psychiatric condition that affects thousands of people worldwide. The absence of biomarkers for BD has resulted in misdiagnosis and ineffective treatment in some patients, causing additional health problems and high costs for health systems. As such, this book evaluates various strategies for sample preparation for proteomic and ionomic studies in order to simplify complex serum samples and allow the quantification of chemical species (proteins and metal ions), which are potential candidates for BD biomarkers. In addition, it describes the development of a new membrane-based methodology for extracting urine proteins to be used in biomarker discovery.
Introduction -- Application of a Proteomic Strategy for the Identification of Differential Proteins Candidates to Biomarkers of Bipolar Disorder -- Application of the Ionomic Strategy to Evaluate Possible Differences in Metal Ion Concentration Between Patients with Bipolar Disorder and other Psychiatric Disorders -- Development of a New Polymer Membrane Based Methodology for Characterization of the Urine Proteome -- Final Conclusion. .
Keywords: Analytical chemistry; Psychobiology; Proteins .; Medicinal chemistry; Analytical Chemistry; Biological Psychology; Protein Biochemistry; Medicinal Chemistry